2015
DOI: 10.1016/j.jastp.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Hot flow anomaly remnant in the far geotail?

Abstract: A hot flow anomaly (HFA) like event was observed by the Solar TErrestrial RElations Observatory (STEREO) in the night side magnetosheath in the far tail in February-March 2007. The magnetic signature of the tangential discontinuity was visible, but the resolution of the plasma ion data is not sufficient for our analysis, so a method is given to identify HFAs without solar wind velocity measurements. The event observed in the night side magnetosheath in the far tail might be the remnant of an HFA event, a not-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Using multiple spacecraft, C.-P. Wang, Liu, et al (2018) found that foreshock transient-driven perturbations in the magnetosheath can propagate with the driver solar wind discontinuity from dayside to midtail, causing the midtail magnetopause to locally move outward. Using STEREO observations, Facskó, Opitz, et al (2015) also found HFA-like perturbations in the far tail magnetosheath (X ∼ −310 R E ). Using Acceleration Reconnection Turbulence & Electrodynamics of Moon's Interaction with the Sun (ARTEMIS) observations, T. Z.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Using multiple spacecraft, C.-P. Wang, Liu, et al (2018) found that foreshock transient-driven perturbations in the magnetosheath can propagate with the driver solar wind discontinuity from dayside to midtail, causing the midtail magnetopause to locally move outward. Using STEREO observations, Facskó, Opitz, et al (2015) also found HFA-like perturbations in the far tail magnetosheath (X ∼ −310 R E ). Using Acceleration Reconnection Turbulence & Electrodynamics of Moon's Interaction with the Sun (ARTEMIS) observations, T. Z.…”
mentioning
confidence: 82%
“…Using STEREO observations, Facskó, Opitz, et al. (2015) also found HFA‐like perturbations in the far tail magnetosheath ( X ∼ −310 R E ). Using Acceleration Reconnection Turbulence & Electrodynamics of Moon’s Interaction with the Sun (ARTEMIS) observations, T. Z. Liu et al.…”
Section: Introductionmentioning
confidence: 91%
“…Recent multipoint observations by Wang et al (2018) found that as the driver discontinuity of a foreshock transient convected tailward with the solar wind, the foreshock transient‐driven perturbations propagated with the discontinuity from the dayside magnetosheath to the midtail magnetosheath (X ~ −30 to −50 R E ), which caused local outward motion of the midtail magnetopause. Additionally, STEREO at X ~ −310 R E also observed HFA‐like perturbations in the far tail magnetosheath (Facskó et al, 2015). These results suggest that foreshock transient‐driven perturbations could continuously disturb the magnetosphere‐ionosphere system from dayside to nightside over timescales of tens of minutes.…”
Section: Introductionmentioning
confidence: 95%
“…Collinson et al [] suggested that the smaller physical size of Cytherian HFAs may simply be a result of them not having as long to form before the current sheet entirely transits the shock, and the HFA is swept off down the magnetotail [e.g., see Facskó et al , ]. The time taken ( τ ) for a current sheet to transit the bow shock from one side to the other (flank to flank) is given by equation .…”
Section: Size and Durationmentioning
confidence: 99%